Kartagener’s Syndrome: A Case Report - Basak, PM; Islam, MN; Sarkar, BC; Islam, MA; Rashed, HM; Islam, Jafor; Das, HS (TAJ: Journal of Teachers Association, 2018)
Abstract not available TAJ 2015; 28(1): 45-47